Effect of different forms of N fertilizers on the hyperaccumulator Solanum nigrum L. and maize in intercropping mode under Cd stress. Issue 70 (30th November 2018) - Huo, Wenmin; Zou, Rong; Wang, Li; Guo, Wei; Zhang, Dujun; Fan, Hongli
Abstract : In the present study, we investigated the effects of different forms of nitrogen fertilizers on the hyperaccumulator Solanum nigrum L. and maize in intercropping mode under cadmium (Cd) stress and explored the physiological response mechanism. Abstract : In the present study, we investigated the effects of different forms of nitrogen fertilizers on the hyperaccumulator Solanum nigrum L. and maize in intercropping mode under cadmium (Cd) stress and explored the physiological response mechanism. This research lays the foundation for the appropriate use of nitrogen (N) fertilizer, reduced costs of ecological restoration, and phytoremediation of environmental pollution by using this intercropping system. The main greenhouse pot experiment was conducted using 1.92 mg kg −1 Cd-contaminated soil. NH4 + –N fertilizer and NO3 − –N fertilizer treatments were performed along with no nitrogen fertilizer treatment as the control. The results indicate that intercropping could decrease the Cd uptake of maize compared with maize monocropping, but the biomass of maize would decrease under the intercropping mode. The application of N fertilizer to the maize– S. nigrum intercropping system could increase the total biomass of maize and S. nigrum . Compared with the NO3 − –N fertilizer treatment, the Cd content of stem, leaf and grain tissues of S. nigrum significantly increased by 9.43%, 22.2%, and 8.33%, respectively, under the NH4 + –N fertilizer treatment. The bioconcentration and translocation factors of S. nigrum significantly increased by 11.1% and 15.3%. Moreover, the Cd content of stem, leaf, and grain tissues of maize decreased by 26.5%, 21.2%, and 21.4%, respectively. The bioconcentration and translocation factors of maize significantly decreased by 38.8% and 46.7%. The application of N fertilizers promoted the accumulation of Cd in maize roots, while Cd content decreased in maize shoots. Compared with NO3 − –N fertilizer, NH4 + –N fertilizer can improve Cd accumulation in various S. nigrum tissues under intercropping, which could reduce Cd accumulation in maize under intercropping. Therefore, the application of NH4 + –N fertilizer is recommended for satisfactory bioremediation when using the Cd-hyperaccumulator S. nigrum and for supporting the safe production of maize in Cd-contaminated soil, thus enabling the goal of simultaneous agricultural production and remediation.